2004
DOI: 10.2134/agronj2004.1364
|View full text |Cite
|
Sign up to set email alerts
|

Soil Surface Property and Soybean Yield Response to Corn Stover Grazing

Abstract: Farmer concern that compaction and/or surface roughness caused paired root growth (Voorhees, 1992), and reduced transby winter grazing of corn (Zea mays L.) crop residues may reduce port of oxygen and nutrients (Scholefield et al., 1985). subsequent soybean [Glycine max (L.) Merr.] yield prompted this 3-yr, on-farm study near Atlantic, IA. Two 19-ha fields with Marshall

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 14 publications
(26 reference statements)
0
50
0
3
Order By: Relevance
“…Nos EUA, Daniel et al (2002) relataram maior densidade em solos de pradaria, em função da carga animal utilizada na pastagem, enquanto Clark et al (2004) não constataram diferença na densidade em quatro solos siltosos em áreas de resteva de milho, pastejadas ou não por bovinos. Flores et al (2007) constataram que o pastejo em Latossolo Vermelho aumentou a densidade e reduziu a porosidade, porém não influenciou o rendimento da soja após o pastejo.…”
Section: Resultsunclassified
“…Nos EUA, Daniel et al (2002) relataram maior densidade em solos de pradaria, em função da carga animal utilizada na pastagem, enquanto Clark et al (2004) não constataram diferença na densidade em quatro solos siltosos em áreas de resteva de milho, pastejadas ou não por bovinos. Flores et al (2007) constataram que o pastejo em Latossolo Vermelho aumentou a densidade e reduziu a porosidade, porém não influenciou o rendimento da soja após o pastejo.…”
Section: Resultsunclassified
“…Esses resultados confirmam os dados de Trein et al (1991), que limitam a 0-0,075 m a camada afetada pelo pisoteio bovino. Também Clark et al (2004), realizando experimento envolvendo pastoreio em resteva de lavoura de milho, em intervalos de 28 dias, encontraram valores de RP de 21 a 44 % superiores, em relação às áreas não-pastejadas. Os valores encontrados nos sistemas P14 e P28 situam-se acima do limite crítico de 2 MPa proposto por Taylor et al (1966).…”
Section: Resultsunclassified
“…Existing research on soil compaction has generally shown minimal effects by livestock grazing corn residue when following recommended management practices (Clark et al, 2004;Maughan et al, 2009;Shaver et al, 2014). Impacts on grain yield were not considered to be a major factor by Nebraska corn producers (Ulmer et al, 2016), which is in agreement with field research that soybean and corn yields following cattle grazing corn residues are similar to nongrazed treatments (Clark et al, 2004;Drewnoski et al, 2016;Stalker et al, 2015;Wilson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%